Anti-obesity potential of Eurycoma longifolia: molecular docking and experimental validation in diet-induced obese rats - Dimas Ikhsan Airlangga; Hanifa Rizky Rahmawati; Triawanti; Muhammad Alrizal Rahman (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Background: Obesity is associated with hyperlipidemia and enhanced adipogenesis mediated by HMGR and GPDH enzymes. Eurycoma longifolia represents a potential natural therapeutic alternative to statins for obesity management. Objective: To investigate the anti-obesity potential of E. longifolia compounds through HMGR and GPDH inhibition using integrated in silico and in vivo approaches. Methods: Molecular docking was performed using AutoDock Vina to evaluate interactions between seven bioactive compounds and HMGR/GPDH proteins. Validation was confirmed by RMSD values below 2 Å. Binding affinities and dissociation constants were analyzed. In vivo study employed Wistar rats fed high-calorie, high-fat diet for 12 weeks, followed by four weeks of E. longifolia extract treatment at varying doses. Body weight and intra-abdominal fat were measured. Results: Three compounds exhibited binding affinities equivalent to atorvastatin against HMGR (-8.4 kcal/mol). Four compounds demonstrated stronger affinity than metformin against GPDH. Extract administration significantly reduced intra-abdominal fat in a dose-dependent manner (p = 0.000). Conclusion: E. longifolia compounds demonstrate dual inhibitory potential against HMGR and GPDH through computational modeling, with experimental validation confirming significant reduction in visceral adiposity in obese rats.